(untitled) (LEARNing Landscapes, 2010)
Canadian and U.S. educational policies in relation to the challenges of urban education have diverged dramatically since the 1960s. This article points to some of the ideas and political processes that lie behind the divergence, and suggests that more comparative analysis of educational policy is both enlightening and important.